Exploration of Spinal Cord Aging–Related Proteins Using a Proteomics Approach. (7th June 2017) - Kamiya, Koshiro; Furuya, Takeo; Hashimoto, Masayuki; Mannoji, Chikato; Inada, Taigo; Ota, Mitsutoshi; Maki, Satoshi; Ijima, Yasushi; Saito, Junya; Kitamura, Mitsuhiro; Ohtori, Seiji; Orita, Sumihisa; et al.
How aging affects the spinal cord at a molecular level is unclear. The aim of this study was to explore spinal cord aging–related proteins that may be involved in pathological mechanisms of age-related changes in the spinal cord. Spinal cords of 2-year-old and 8-week-old female Sprague-Dawley rats were dissected from the animals. Protein samples were subjected to 2-dimentional polyacrylamide gel electrophoresis followed by mass spectrometry. Screened proteins were further investigated with immunohistochemistry and Western blotting. Among the screened proteins, we selected α-crystallin B-subunit (αB-crystallin) and peripherin for further investigation because these proteins were previously reported to be related to central nervous system pathologies. Immunohistochemistry and Western blotting revealed significant upregulation of αB-crystallin and peripherin expression in aged rat spinal cord. Further exploration is needed to elucidate the precise mechanism and potential role of these upregulated proteins in spinal cord aging processes.